Pengaruh Kombinasi dan Rasio Pelarut Terhadap Hasil Ekstraksi Minyak dari Serabut Kelapa Sawit - Rozi, Fachrul; Abram, Paulus Hengky; Diah, Anang Wahid M. (Universitas Tadulako, 2018)
This study aimed to determine the combinations and ratios of appropriate solvents to obtain the optimal mass of palm oil. Extracting the oil from palm fibers was conducted using soxletation method. Extraction is a way to get oil in a high amount and good quality by using an appropriate solvent. The weight of oils obtained from the volume ratios variable of solvents at 100:0, 70:30, 50:50, 30:70, and 0:100 were 0.446 ± 0.063 g, 0.379 ± 0.022 g, 0.295 ± 0.012 g, 0.276 ± 0.045 g, and 0.183 ± 0.054 g, respectively. This study showed the combination of the types and ratios of solvents toward extraction of oil, and the optimal oil mass was produced from n-hexane solvent.